EDUCATION IN THE FIELD OF ENERGY EFFICIENCY IN SERBIA-SURVEY RESULTS AND ANALYSIS - Jovanović, Bojana; Božanić, Vojislav; Jovanović, Bojan (Journal of Applied Engineering Science, 2013)
In the Balkan region and in the territory of the Republic of Serbia, the energy consumption in relation to gross domestic product is huge. The Republic of Serbia consumes two to three times more energy than the gross domestic product, compared with the average in the European Union. At the beginning of 2013, on the territory of the Republic of Serbia, will be announced the Law on rational use of energy, which is currently in draft form. Adoption of the Law is a step in Serbia’s accession to the EU, because the Law will basically have taken a European directive on energy efficiency. In order to determine the extent to which the concept of energy efficiency is presented in the formal and informal education, as well as knowledge of this area in general, the survey was done. This paper describes a results of survey that was done with the aim of gaining information about education in the field of energy efficiency in formal and informal education systems in Serbia, as well as how much are the citizens familiarity with the term. This paper shows the questionnaire which was distributed to the respondents. For easily and quickly collecting the necessary data, we used the on-line questionnaire. The questionnaire was designed as a web application. The survey was conducted on a sample of 200 respondents, from september to december 2012. After the structure of the respondents, the results of research and analysis are presented in this paper, with one proposed research in future. Education in the field of energy efficiency in Serbia – survey results and analysis